SAMUDERA®: a simulation blueprint for sustainability action-experiential learning across disciplines - Mohd, Siti Hadija (UTP Press, 2025)
Simulation games are increasingly recognised as versatile tools for promoting sustainability education across disciplines. This paper reviews SAMUDERA®, a sustainability simulation game adapted from the Fish Banks game by the System Dynamics Society, tailored to local Malaysian contexts. SAMUDERA® has been implemented with university students, government agencies, private companies, and community groups. This paper discusses its development, integration with action-experiential learning pedagogy, and application across diverse fields. It also reflects on the simulation’s challenges, strengths, and potential to enhance decision-making and sustainability practices. Insights into the game highlight the importance of strategic preparation by facilitators, including the use of engaging physical setups and clear instructions. The paper also highlights the significance of collaboration, active participation, and post-game discussions in achieving impactful learning outcomes and catalysing behaviour change. Furthermore, the study reflects on SAMUDERA®’s adaptability across management, business, policymaking, social sciences, and fisheries education. Future directions for improving the simulation’s content include exploring advanced topics like climate change impacts, fisheries certification, and the role of marine protected areas. Overall, SAMUDERA® demonstrates its potential as an effective educational tool for sustainability education across disciplines and diverse participant groups.